NLP AND USE OF MODAL VERBS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Difficulties with the usage of Modal verbs – in particular, perfect forms of them – as well as clear solutions to overcome them are shown in this article. Two of the most effective NLP strategies (grouping, native language translation) can help English language learners to use Modal verbs in their daily speech easily.